Implementation of Competency-Based Leadership Models in Enhancing Academic Achievement - Muhammad Zaid Al Ghazi (Program Studi Doktor Manajemen Pendidikan Islam, Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Effective leadership is widely recognized as a cornerstone for improving student academic outcomes and institutional quality. This study investigates the implementation of competency-based leadership models at Pondok Roudlatu Ta’limil Qur’an Gresik and examines its role in enhancing student academic achievement. Using a qualitative case study approach, data were gathered through in-depth interviews, participant observation, and document analysis involving the principal, teachers, and staff. The findings reveal that the principal’s proficiency in managerial, professional, social, and personality competencies facilitates a robust educational environment through strategic planning, merit-based teacher placement, and continuous academic supervision. These leadership practices successfully cultivate a positive academic culture characterized by high student motivation and improved teacher instructional quality. While structural barriers such as administrative workloads and infrastructure gaps persist, the principal’s transition to professionalized governance ensures institutional resilience. This research emphasizes that strengthening principal competencies is vital for sustaining educational excellence in modernized Islamic boarding schools.